Interculturality and ethnomathematics: theoretical perspectives for the formation of indigenous teachers of the degree in mathematics - Santino, Fernando Schlindwein; Teixeira , Leny Rodrigues Martins (Seven Editora, 2023)
In this text we approach the issue of Interculturality and Ethnomathematics as perspectives for the formation of indigenous teachers of the degree in Mathematics, aiming to present the ideas of several authors who have based this issue. The reported research is framed as bibliographic research, whose authors constitute references to analyze some problems of teacher education, among which the valorization of indigenous mathematical knowledge when compared with Eurocentered knowledge. It seems that Interculturality and Ethnomathematics are theoretical perspectives that can contribute "to" and "with" the recognition and appreciation of indigenous culture and the struggle for a differentiated and more human indigenous school education. In this sense, the training of indigenous teachers becomes more complex, since, in addition to teaching future teachers the mathematical concepts/contents, it has to prepare them to act in two worlds, indigenous and non-indigenous. The training of indigenous teachers is, therefore, conditioned by multiple factors and because it is a relatively recent theme of research, requires much deepening and investment in the process of building a teaching practice that respects indigenous culture. Teacher training, based on Interculturality and Ethnomathematics, may become one of the ways to "keep moving" so that indigenous undergraduates and teachers can overcome the current challenges of the devaluation of their culture. DOI: https://doi.org/10.56238/devopinterscie-025